2022
DOI: 10.1016/s2542-5196(21)00296-5
|View full text |Cite|
|
Sign up to set email alerts
|

Optimising the deployment of vector control tools against malaria: a data-informed modelling study

Abstract: Background Concern that insecticide resistant mosquitoes are threatening malaria control has driven the development of new types of insecticide treated nets (ITNs) and indoor residual spraying (IRS) of insecticide. Malaria control programmes have a choice of vector control interventions although it is unclear which controls should be used to combat the disease. The study aimed at producing a framework to easily compare the public health impact and costeffectiveness of different malaria prevention measures curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…In general, the nets which replaced study nets were obtained from periodic governmental net distributions in the study area. It is of key importance that manufacturers produce more durable nets, which could potentially be achieved with a small increase in unit price (18, 42) by reinforcing seam and net lower mid-zone or bottom part which is vulnerable to abrasion (S3 Table).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the nets which replaced study nets were obtained from periodic governmental net distributions in the study area. It is of key importance that manufacturers produce more durable nets, which could potentially be achieved with a small increase in unit price (18, 42) by reinforcing seam and net lower mid-zone or bottom part which is vulnerable to abrasion (S3 Table).…”
Section: Discussionmentioning
confidence: 99%
“…The development of stronger net material would also improve net usage if holes were to appear more slowly and, finally, community sensitisation to improve care and repair could also reduce the rate of textile degradation [42, 43], and maintain higher coverage, thereby increasing the length of time between distributions. Intervening in each of these parameters will alter the relative cost-effectiveness of products and the viability of each strategy [44].…”
Section: Discussionmentioning
confidence: 99%
“…Only LLINs may have been less effective around that time, approx. two years after the mass campaign in 2014, as their integrity and insecticide bio-efficacy is known to decrease over time [66,67]. This, alongside the heavy rains in 2017, may be a reason for the slightly increased incidence rates observed that year.…”
Section: Discussionmentioning
confidence: 99%